(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In this paper, considering both a modular metric space and a generalized metric space in the feeling of Jleli and Samet, we present another idea of generalized modular metric space. At that point we present a few examples demonstrating that the generalized modular metric space incorporates some sort of metric structures. At long last, we give some fixed point results to both withdrawal and quasicontraction type mappings on generalized modular metric spaces.